Classroom Interaction Analysis in the EFL Speaking Class: A Study at English Department of IAIN Imam Bonjol Padang - Elismawati Elismawati (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2016)
The success of teaching depends to a large extent on the way teachers talk and interactions that occur between teachersand students. The happening of interaction is affected directly by ways of teacher talk. This study entitles “Classroom InteractionAnalysis in the EFL Speaking Class” aimed at analyzing the categories of teacher talk, student talk and classroom interaction typesused during EFL speaking class. The research employed a qualitative design and applied a case study. Subjects of the research werean English teacher and 35 students at the second semester at English Department of IAIN Imam Bonjol Padang. The data weregained through naturalistic observation and document analysis. The data were analyzed by using Foreign Language Interaction(FLINT) system. The findings revealed that both teacher and students applied all categories of talk as mentioned in FLINT systemand classroom interaction types.